Multicenter Evaluation of Candida QuickFISH BC for Identification of Candida Species Directly from Blood Culture Bottles - Abdelhamed, Ayman M. (J Clin Microbiol, 2015)
Candida species are common causes of bloodstream infections (BSI), with high mortality. Four species cause >90% of Candida BSI: C. albicans, C. glabrata, C. parapsilosis, and C. tropicalis. Differentiation of Candida spp. is important because of differences in virulence and antimicrobial susceptibility. Candida QuickFISH BC, a multicolor, qualitative nucleic acid hybridization assay for the identification of C. albicans (green fluorescence), C. glabrata (red fluorescence), and C. parapsilosis (yellow fluorescence), was tested on Bactec and BacT/Alert blood culture bottles which signaled positive on automated blood culture devices and were positive for yeast by Gram stain at seven study sites. The results were compared to conventional identification. A total of 419 yeast-positive blood culture bottles were studied, consisting of 258 clinical samples (89 C. glabrata, 79 C. albicans, 23 C. parapsilosis, 18 C. tropicalis, and 49 other species) and 161 contrived samples inoculated with clinical isolates (40 C. glabrata, 46 C. albicans, 36 C. parapsilosis, 19 C. tropicalis, and 20 other species). A total of 415 samples contained a single fungal species, with C. glabrata (n = 129; 30.8%) being the most common isolate, followed by C. albicans (n = 125; 29.8%), C. parapsilosis (n = 59; 14.1%), C. tropicalis (n = 37; 8.8%), and C. krusei (n = 17; 4.1%). The overall agreement (with range for the three major Candida species) between the two methods was 99.3% (98.3 to 100%), with a sensitivity of 99.7% (98.3 to 100%) and a specificity of 98.0% (99.4 to 100%). This study showed that Candida QuickFISH BC is a rapid and accurate method for identifying C. albicans, C. glabrata, and C. parapsilosis, the three most common Candida species causing BSI, directly from blood culture bottles.